From antiquity to contemporary times: how olive oil by-products and waste water can contribute to health - Albini, Adriana; Albini, Francesca; Corradino, Paola; Dugo, Laura; Calabrone, Luana; Noonan, Douglas M. (Frontiers in Nutrition, 2023)
Since antiquity, numerous advantages of olive oil and its by-products have been recognized in various domains, including cooking, skincare, and healthcare. Extra virgin olive oil is a crucial component of the Mediterranean diet; several of its compounds exert antioxidant, antiproliferative, anti-angiogenic and pro-apoptotic effects against a variety of cancers, and also affect cellular metabolism, targeting cancer cells through their metabolic derangements. Numerous olive tree parts, including leaves, can contribute metabolites useful to human health. Olive mill waste water (OMWW), a dark and pungent liquid residue produced in vast amounts during olive oil extraction, contains high organic matter concentrations that may seriously contaminate the soil and surrounding waters if not managed properly. However, OMWW is a rich source of phytochemicals with various health benefits. In ancient Rome, the farmers would employ what was known as amurca, a mulch-like by-product of olive oil production, for many purposes and applications. Several studies have investigated anti-angiogenic and chemopreventive activities of OMWW extracts. The most prevalent polyphenol in OMWW extracts is hydroxytyrosol (HT). Verbascoside and oleuperin are also abundant. We assessed the impact of one such extract, A009, on endothelial cells (HUVEC). A009 was anti-angiogenic in several in vitro assays (growth, migration, adhesion) and inhibited angiogenesis in vivo, outperforming HT alone. A009 showed potential cardioprotective effects mitigating cardiotoxicity induced by chemotherapy drugs, commonly used in cancer treatment, and reducing up-regulation of pro-inflammatory markers in cardiomyocytes. Extracts from OMWW and other olive by-products have been evaluated for biological activities by various international research teams. The results obtained make them promising candidates for further development as nutraceutical and cosmeceutical agents or dietary supplement, especially in cancer prevention or even in co-treatments with anti-cancer drugs. Furthermore, their potential to offer cardioprotective benefits opens up avenues for application in the field of cardio-oncology.